2022
DOI: 10.3389/fcvm.2022.892335
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Management of Dyslipidemia in Patients With Cancer

Abstract: Patients with cancer are now living longer than ever before due to the growth and expansion of highly effective antineoplastic therapies. Many of these patients face additional health challenges, of which cardiovascular disease (CVD) is the leading contributor to morbidity and mortality. CVD and cancer share common biological mechanisms and risk factors, including lipid abnormalities. A better understanding of the relationship between lipid metabolism and cancer can reveal strategies for cancer prevention and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 93 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…Among the drugs used for endocrine therapy, AIs are shown to increase the risk of dyslipidemia, hyperglycemia, metabolic syndrome and hypertension, while ADTs are associated with hypertension, hyperglycemia and metabolic syndrome ( 4 ). In addition to these, other classes related to the development of dyslipidemias are anthracyclines, VEGH inhibitors, L-asparginase, JAK 1/2 inhibitor, Bexarotene, and Capcitabine ( 5 ).…”
Section: Cancer Care and Its Cardiovascular Effectsmentioning
confidence: 99%
“…Among the drugs used for endocrine therapy, AIs are shown to increase the risk of dyslipidemia, hyperglycemia, metabolic syndrome and hypertension, while ADTs are associated with hypertension, hyperglycemia and metabolic syndrome ( 4 ). In addition to these, other classes related to the development of dyslipidemias are anthracyclines, VEGH inhibitors, L-asparginase, JAK 1/2 inhibitor, Bexarotene, and Capcitabine ( 5 ).…”
Section: Cancer Care and Its Cardiovascular Effectsmentioning
confidence: 99%
“…Chemotherapy was found to have negative impacts on quality of life and lipid levels, as reported in previous studies. [42][43][44][45] A study [46] indicated that chemotherapy caused notable changes in plasma lipid and lipoprotein levels in individuals with breast cancer, potentially through gene modulation. Intriguingly, the prevalence of liver function abnormalities was higher in US-diagnosed HS patients, compare to USE-diagnosed HS cases.…”
Section: Discussionmentioning
confidence: 99%
“…Higher hyperlipidemia rates were reported in patients who survived testicular cancer, suggesting that RT and/or chemotherapy also affect the lipid profile (de Jesus et al, 2022).…”
Section: Cardiovascular Adverse Effects Of Radiotherapymentioning
confidence: 96%